European Surveillance System on Contact Allergies (ESSCA): polysensitization, 2009–2014. (22nd February 2018) - Dittmar, Daan; Uter, Wolfgang; Bauer, Andrea; Fortina, Ana B.; Bircher, Andreas J.; Czarnecka‐Operacz, Magdalena; Dugonik, Aleksandra; Elsner, Peter; Gallo, Rosella; Ghaffar, Sharizan A.; Giménez‐Arnau, Anna; Johnston, Graham A.; et al.
Abstract : Background: Polysensitization, defined as being allergic to three or more haptens from the European baseline series, is considered to reflect increased susceptibility to developing a contact allergy, and is likely to be associated with an impaired quality of life. Objectives: To evaluate the prevalences of polysensitization across Europe and to analyse factors associated with polysensitization. Methods: Patch test data collected by the European Surveillance System on Contact Allergies (ESSCA; www.essca‐dc.org ) in consecutively patch tested patients from January 2009 to December 2014, comprising 11 countries and 57 departments, were retrospectively analysed. Results: A total of 86 416 patients were available for analysis, showing a standardized prevalence of polysensitization of 7.02%, ranging from 12.7% (Austria) to 4.6% (Italy). Allergen pairs with the strongest association are reported for the total population, for South Europe, and for North/Central Europe. Overall, polysensitized patients showed a higher percentage of extreme (+++) positive patch test reactions than oligosensitized patients. Female sex, occupational dermatitis and age > 40 years were risk factors for polysensitization. Conclusions: The varying prevalences of polysensitization across Europe most likely reflect differences in patient characteristics and referral patterns between departments. Known risk factors for polysensitization are confirmed in a European dermatitis population. Abstract :